Comparison of mucosal and mucoperiosteal wound cover for the treatment of medication-related osteonecrosis of the jaw lesions: a retrospective cohort study - Nonnenmühlen, Nicola; Ristow, Oliver (Clinical oral investigations, 2019)
ObjectivesActually, there is no detailed guidance on how to deal with wound closure after surgical removal of medication-related osteonecrosis of the jaw (MRONJ) lesions. This study attempts to compare the difference in outcome between the mucosal and the mucoperiosteal flap closure after surgery.Patients and methodsIn this retrospective monocentric cohort study, patients (n = 61; 35 female/26 male) suffering from MRONJ and requiring surgical therapy at the University of Aachen between 2013 and 2015 were included. Due to intra-institutional variances, one group was treated with the mucosal, the other group with the mucoperiosteal technique. The success rate, i.e., mucosal closure and no relapse at the point of follow-up, was evaluated and compared. All patients were clinically investigated for the postoperative follow-up during a special consultation appointment.ResultsThe success rates between the different techniques after 2 years follow-up were very similar. In the group of mucosal wound closure, 22 of 29 (75.86%) patients revealed mucosal integrity without signs of MRONJ. The rate in the mucoperiosteal wound closure group was almost identical (24 of 32 (75%)).ConclusionNo differences in the success rates between the two different techniques could be evaluated.Clinical relevanceThe results of this study suggest that the complete removal of the necrotic bone might have a higher impact on the success rates than the technique of the wound closure. Due to the fact that the mucoperiosteal wound closure technique offers a better overview of the extent of the MRONJ lesion, the authors advise to use this technique.
Published online: 22 April 2018
Gesehen am 19.07.2019